Why consumers disagree about future inflation - Naveen Rai; Patrick Sabourin (Bank of Canada, 2023)
Since 2022, consumer inflation expectations have shifted, with a significant increase in those expecting high inflation in the coming year and a surge in those expecting deflation further in the future. Using data from the Canadian Survey of Consumer Expectations, this paper seeks to assess the factors that influence people to expect high inflation, moderate inflation or deflation. While expectations of high inflation are largely based on perceptions about current inflation, most of those anticipating future deflation do not see the Canadian economy as currently deflationary. Rather, their deflationary outlook since 2022 has hinged on the belief that current inflation-inducing supply and demand factors such as supply chain issues are temporary and will reverse, triggering price declines.
Keywords: C83; D84; E31; 330; Inflation and prices